Patient selection for cytoreductive surgery and HIPEC for the treatment of peritoneal metastases from colorectal cancer - Simkens GA; Rovers KP; Nienhuijs SW; de Hingh IH (Cancer Management and Research, 2017)
Geert A Simkens, Koen P Rovers, Simon W Nienhuijs, Ignace H de Hingh Department of Surgical Oncology, Catharina Cancer Institute, Eindhoven, The Netherlands Abstract: Cytoreductive surgery (CRS) and hyperthermic intraperitoneal chemotherapy (HIPEC) is a viable option for selected patients with peritoneal metastases (PM) from colorectal origin, resulting in long-term survival and even cure in some cases. However, adequate patient selection for this treatment is currently one of the major challenges. The aim of this review is to provide a comprehensive overview of clinically relevant factors associated with overall survival. This may help to guide clinicians through the complex interplay of patient, tumor, and treatment characteristics to adequately select patients who benefit the most from this extensive surgical treatment. First, basic principles of colorectal PM and the CRS and HIPEC treatment will be discussed. According to available literature, especially extent of peritoneal disease, completeness of cytoreduction, and signet ring cell histology have great influence on the outcome after CRS and HIPEC. Other factors that seem to have a negative prognostic value are the presence of liver metastases and the absence of treatment with neo-adjuvant systemic therapy. Prognostic models combining the above-mentioned factors, such as the Colorectal Peritoneal Metastases Prognostic Surgical Score nomogram, may provide clinically relevant tools to use in everyday practice. Keywords: cytoreductive, hyperthermic intraperitoneal chemotherapy, colorectal neoplasms, peritoneal metastases, prognostic factors